Characterization of Histone H3 Gene Family Reveals That GmHH3-3 is Associated With Higher Seed Weight in Glycine max - Fatima, Chahat; Tahir, Muhammad Hammad Nadeem; Ikram, Rao Muhammad; Khan, Zulqurnain; Sajjad, Muhammad; Qanmber, Ghulam; Darwish, Essam; Geng, Zhide; Xiangkuo, Gao; Ur Rehman, Shoaib (Frontiers in Genetics, 2022)
The main function of histone protein is to provide support to the structure of chromosomes. It helps in binding a long thread of DNA into a more condensed shape to fit into the nucleus. From histone variants, histone H3 (HH3) plays a crucial role in plant growth and development. Characterization of histones has not been reported in Glycine max till now. The objective of this study was to characterize the HH3 gene family for molecular breeding of G. max. In this study, 17 HH3 members in G. max were identified by performing local BLASTp using HH3 members from Arabidopsis as a query. Phylogenetic analysis classified HH3 genes in seven clades. Sequence logo analysis among Arabidopsis thaliana, Oryza sativa, and Glycine max showed a higher level of similarity in amino acids. Furthermore, conserveness of G. max HH3 genes was also confirmed by Gene Structure Display. Ten paralogous gene pairs were identified in GmHH3 genes in the Glycine max genome by conducting collinearity analysis. G. max HH3 genes have experienced strong purifying selection pressure, with limited functional divergence originating from the segmental and whole-genome duplication, as evidenced by the Ka/Ks ratio. The KASP marker was developed for GmHH3-3 gene. Genotyping was performed on 46 G. max genotypes. This differentiation was based upon the presence of either GmHH3-3-C or GmHH3-3-T allele in the CDS region. The results showed that G. max accessions containing the GmHH3-3-T allele at respective locus showed higher thousand seed weight than that of those accessions that contain the GmHH3-3-C allele. This research provides the basic information to further decipher the function of HH3 in soybean.